ANALISIS DAMPAK KEBIJAKAN HARGA GABAH TERHADAP HARGA GABAH KERING GILING DI TINGKAT PENGGILINGAN PADI - Rahmanto, Muhammad Ikhwan (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2012)
The aim of this study was to compare the impact of the basic price policy and the purchase of governement price policy against the rice prices in the market (milling ) in the period 1970-1997 and the period 1998-2009. The data of this study are secondary data sourced from BPS, Bulog, and the results of relevant studies, including data on the history and analysis of rice policy, the data of rice price policy covers the basic prices and the purchase of government price period 1969 - 2009, and data of rice price data at the milling level period 1969-2009. Data were analyzed with simple regression analysis . The results of this study are the basic prices and the purchase of government price for dry unhusked at Mills always increase adjust to market developments. Basic rice price policy 1970-1978 has been effective. Basic rice price policy 1997-2009 is still effective. Rice price policy of (1970-1997) is more effective than the post-New Order (1998-2009).